Dampak Dari Perusahaan Multinasional Dalam Mempengaruhi Sumber Hukum Internasional - Izaz Vito Adyuta (Pusat Riset dan Inovasi Nasional, 2025)
the impact of multinational corporations (MNCs) in influencing the sources of international law. MNCs play a significant role in the global economy, especially in developing countries, which require foreign investment. The existence of MNCs contributes to the formation and amendment of international treaties, even though these companies are not directly recognized as subjects of international law. The sources of international law evolve over time, including international treaties, international custom, court decisions, as well as scholarly teachings. While MNCs do not have the capacity to litigate in the International Court of Justice, they can play a role in international arbitration and influence the legal policies of the countries in which they operate. The influence of MNCs on the economies of developing countries often leads to the inability of those countries to enforce national laws, due to fears of loss of investment. Therefore, while there is debate over the status of MNCs in international law, they still have a major impact in shaping and influencing the rules of international law through economic cooperation and international treaties.